(untitled) (Nóema, 2013)
The essay investigates the problem of Self-construction in latest Nietzsche’s thought and its relation with the question of decadence. The identity crisis of Western civilisation, the break-up of the ethical and cultural ground of modern European societies, become at the same time the opportunity for a radical renewal of humanity, the starting point for a great «anthropotechnical experiment» aimed at shaping a new human «type», a new model for a Post-Christian ethos.